Rate of Adriamycin Resistance Associated (ARA) long Noncoding RNA Expression in Sample of Hepatitis B Virus Iraqi Patients - Osama Mohammed Hasan (College of Pharmacy / Mustansiriyah University, 2024)
Numerous biological processes, including epigenetics regulation, control of cell cycle, beside transcriptional, translational and regulation of genes expression, have been linked to long non-coding RNAs lncRNAs . the disruption of expression for lncRNAs are important early stages in in hepatitis B virus disease. Objectives: In order to investigate ARA lncRNA production in Hepatitis B   patients, analyze its clinical importance, and examine the possible value as a predictive biomarker, Amplification of Adriamycin Resistance Associated Lnc-RNA and Glyceraldehyde 3-phosphate dehydrogenase (reference gene) was done by two steps reverase- transcriptase polymerase chain reaction ,No significant difference P = 0.566 was observed in the Adriamycin Resistance Associated lncRNA serum levels between chronic hepatitis B virus patient  and    control ,In the patients group  with chronic HBV )infection, the expression of  Adriamycin Resistance Associated lncRNAs was elevated to the 2 fold.